2002
DOI: 10.1086/340828
|View full text |Cite
|
Sign up to set email alerts
|

Humanlike Immune Response of Human Leukocyte Antigen–DR3 Transgenic Mice to Staphylococcal Enterotoxins: A Novel Model for Superantigen Vaccines

Abstract: This study examined the biologic responses of transgenic mice expressing human leukocyte antigen (HLA)-DR3 and human CD4 molecules, in the absence of murine major histocompatibility complex (MHC) class II molecules (Ab(0)), to staphylococcal enterotoxins (SEs) and evaluated protective immunity of a nonsuperantigen form of SEB against wild-type holotoxin. HLA-DR3 transgenic mice responded to several log lower concentrations of SEs and secreted higher levels of proinflammatory cytokines than did wild-type mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
56
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 52 publications
3
56
0
1
Order By: Relevance
“…By contrast, the humanized HLA class II-tg mice have shown high sensitivity to bacterial SAgs; T cells from these mice respond vigorously to bacterial SAgs in a way similar to human T cells without any manipulation, suggesting a SAg presentation pattern comparable to that in humans (24,25). Several studies have used HLA-tg mice to investigate immune responses to SAgs and SAgproducing bacteria (20, 24 -26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the humanized HLA class II-tg mice have shown high sensitivity to bacterial SAgs; T cells from these mice respond vigorously to bacterial SAgs in a way similar to human T cells without any manipulation, suggesting a SAg presentation pattern comparable to that in humans (24,25). Several studies have used HLA-tg mice to investigate immune responses to SAgs and SAgproducing bacteria (20, 24 -26).…”
Section: Discussionmentioning
confidence: 99%
“…This difference relates, in part, to the lower binding affinity of SAgs to murine MHC class II as compared with human HLA class II (21). The advent of the HLA class II transgenic (HLA-tg) mice provided an opportunity to study the pathogenesis of GAS in a readily manipulated animal model with a sensitivity to SAgs similar to that of humans (22)(23)(24)(25)(26). Indeed, several studies have shown that HLA-tg mice mount potent responses to GAS SAgs (20,23,25,27,28).…”
mentioning
confidence: 99%
“…Challenging HLA-II transgenic mice with SAgs thorough several different routes elicits robust SIRS and renders them highly susceptible to TSS. [40][41][42][43][44][45][46][47][48][49] One of our HLA-II transgenic lines that expresses HLA-DR3 is extremely sensitive to SEB. HLA-DR3 transgenic mice readily die of SEB-induced TSS without D-galN sensitization.…”
mentioning
confidence: 99%
“…This synergistic action was observed whether the mouse antibodies or chimeric equivalents of the antibody pair were used. However, because it is well established that SEB-mediated effects are seen at much lower toxin concentrations in systems bearing human rather than mouse class II MHC (11,14), it was important to determine the ability of our pair of chimeric antibodies to neutralize SEB in HLA-DR3 transgenic mice, a more demanding and humanlike model system than conventional mice (11,44,45,50,51). Both chimeric antibodies effected neutralization in this transgenic model and, when used together, were synergistic in their neutralization of SEB in cultures derived from HLA-DR3 transgenic mice.…”
mentioning
confidence: 99%